Farmer Participatory Vatidation of Indigenous Technical Knowledge in Agriculture - R.N. Padaria, Baldeo Singh, Jitendra Kumar, B.M. Sharma and M. Pathak, (Indian Journal of Extension Education, 2009)
Indigenous technical knowledge has assumed greater significance in search of eco-friendly practicesfor sustainable agriculture. The present study made an attempt to develop mechanism of participatory validationof the potential of indigenous technical knowledge. Two ITK of managing gundhi bug with exffacts of garlicand tobacco mixed with washing powder and management of termites with lime and salt were subjected tovalidation vis-d-vis the recommended practices for the respective pest. Though the trials showed better efficacyof recommended practices in comparison to indigenous practices for management of gundhi bug in rice andtermite in sugarcane; the participatory on-farm validation trials helped farmers to understand the techniques offield experimentation, data record keeping, analysis and drawing logical conclusions besides attribution processof cause and effect relationship. Dialogue and working with scientists enhanced the confidence of farmers andmotivated them to take up experimentation with sound methodology and validate other technologies and ownpractices with scientific rationality'